The Effects of Pregnancy on the Pulmonary Immune Response in a Mouse Model of LPS-Induced Acute Lung Injury - Rieck, Rebecca E.; Bivona, Joseph J., III; Hoyt, Laura R.; Ventrone, Sebastian; Kokoszynska, Marta; Bonney, Elizabeth A.; Suratt, Benjamin T. (American Journal of Perinatology, 2023)
Objective This study evaluated the effect of pregnancy on the pulmonary innate immune response in a mouse model of acute lung injury (ALI) using nebulized lipopolysaccharide (LPS).Study Design Pregnant (day 14) C57BL/6NCRL mice and nonpregnant controls received nebulized LPS for 15 minutes. Twenty-four hours later, mice were euthanized for tissue harvest. Analysis included blood and bronchoalveolar lavage fluid (BALF) differential cell counts, whole-lung inflammatory cytokine transcription levels by reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR), and whole-lung vascular cell adhesion molecule 1 (VCAM-1), intercellular adhesion molecule 1 (ICAM-1), and BALF albumin by western blot. Mature bone marrow neutrophils from uninjured pregnant and nonpregnant mice were examined for chemotactic response using a Boyden chamber and for cytokine response to LPS by RT-qPCR.Results In LPS-induced ALI, pregnant mice had higher BALF total cell (p < 0.001) and neutrophil counts (p < 0.001) as well as higher peripheral blood neutrophils (p < 0.01) than nonpregnant mice, but a similar increase (as compared with unexposed mice) in airspace albumin levels. Whole-lung expression of interleukin 6, tumor necrosis factor-α (TNF-α), and keratinocyte chemoattractant (CXCL1) was also similar. In vitro, marrow-derived neutrophils from pregnant and nonpregnant mice had similar chemotaxis to CXCL1 and N-formylmethionine-leucyl-phenylalanine, but neutrophils from pregnant mice expressed lower levels of TNF (p < 0.001) and CXCL1 (p < 0.01) after LPS stimulation. In uninjured mice, VCAM-1 was higher in lungs from pregnant versus nonpregnant mice (p < 0.05).Conclusion In this model, pregnancy is associated with an augmented lung neutrophil response to ALI without increased capillary leak or whole-lung cytokine levels relative to the nonpregnant state. This may stem from increased peripheral blood neutrophil response and intrinsically increased expression of pulmonary vascular endothelial adhesion molecules. Differences in lung innate cell homeostasis may affect the response to inflammatory stimuli and explain severe lung disease in respiratory infection during pregnancy.Key Points
Keywords: pulmonary immune; maternal lung; mouse model; lung injury